Elevating the english language teaching learning process: Creative integration of technology to promote 21st century skills in the classroom (2023)
This report aims to detail my experience as a pre-service teacher during my teaching practicum at Institución Educativa María Reina (I.E María Reina), spanning the seventh and eighth semesters. My primary responsibilities included developing lesson plans and educational materials for grades six through eleven, under the guidance of my mentor teachers. Additionally, I assisted in various classroom activities, addressing both student and teacher needs. This report will also present key information about the school, including student demographics, class sizes, and the school's location. Moreover, I will discuss the specific characteristics of the classes, emphasizing their significance in the teaching process. The report concludes with a personal reflection on my eight-month journey, highlighting my growth and insights gained throughout the practicum.